1997
DOI: 10.1093/gerona/52a.3.b159
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Peripheral Vascular Disease in Elderly Subjects Using Optical Spectroscopy

Abstract: The purpose of this study was to determine the usefulness of near-infrared spectroscopy (NIRS) measurements to identify peripheral vascular disease (PVD). Usefulness was determined by the frequency of a successful test, as well as comparison with standard clinical assessments. Study subjects (N = 117, mean age = 67.8 +/- 8.1 yrs) responded to a free screening for PVD. NIRS was used to measure the relative O2 saturation of hemoglobin in the soleus muscle. The time to 1/2 recovery of O2 saturation (O2T1/2) was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 18 publications
2
59
0
2
Order By: Relevance
“…In addition, according to McCully et al (1997), unless the BMI [height (m)/weight (kg 2 )] is below 32, NIRS measurements cannot be made. In the present study, the subjects' BMI values (21.2±1.3) were quite small and its range was narrow.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, according to McCully et al (1997), unless the BMI [height (m)/weight (kg 2 )] is below 32, NIRS measurements cannot be made. In the present study, the subjects' BMI values (21.2±1.3) were quite small and its range was narrow.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, regional differences could result not only from regional differences in intramuscular pressure, but also from disease. Atherosclerosis can significantly reduce oxygen delivery to skeletal muscle [17][18][19][20], and the progression of atherosclerosis is unevenly distributed among conduit arteries [21]. Thus the development of a new noninvasive method for determining regional differences in oxygen status in humans is of great potential value.…”
mentioning
confidence: 99%
“…In [28] it is demonstrated that measuring O 2 Hb and HHb with a NIRS device can be used as an indicator for peripheral vascular disease (PVD).…”
Section: Introductionmentioning
confidence: 99%